A case of nimesulide induced toxic epidermal necrolysis - Xaviar, Suja; Ravichandran, Mirunalini (International Journal of Basic & Clinical Pharmacology, 2020)
Toxic epidermal necrolysis (TEN) is a rare life-threatening drug-induced mucocutaneous skin disease with a mortality rate of approximately 30%. Nimesulide is a preferential cyclo-oxygenase (COX-2) inhibitor which is frequently used for its antipyretic, anti-inflammatory and analgesic activity. Here, we report a case of nimesulide induced toxic epidermal necrolysis in a 57 years old male patient. This patient was admitted in the hospital with symptoms of epidermal sloughing and fluid filled blisters all over the body following over the counter intake of nimesulide for fever. The drug was promptly stopped, and patient was managed with steroids, antibiotics and other adequate supportive measures. The patient showed significant recovery following stoppage of drug and adequate management. This case highlights the importance of nimesulide and other NSAIDs as possible cause of TEN.